Green Supply Chain Marketing: Trends and Research Evolution - Frans Sudirjo; Rani Eka Arini; Salwa Aulia Novitasari (Westscience Press, 2026)
This study aims to map the intellectual structure, research trends, and evolution of Green Supply Chain Marketing through a bibliometric analysis of scholarly publications indexed in the Scopus database. Using VOSviewer as an analytical tool, the study examines keyword co-occurrence, overlay visualization, density mapping, co-authorship networks, institutional collaboration, and country-level partnerships to identify dominant themes and emerging research directions. The findings reveal that the field has evolved from an operational focus on environmental management and green manufacturing toward a strategic integration of marketing, sustainability, and supply chain management. Core research clusters highlight the growing importance of green marketing strategies, decision making, and sustainability-driven innovation in shaping competitive advantage. Overlay analysis indicates that recent studies increasingly emphasize consumer attitudes, government roles, and strategic marketing approaches, reflecting a shift toward market-oriented sustainability practices. Collaboration analysis shows that China and India serve as major contributors to global research output, while cross-institutional collaboration remains relatively fragmented, suggesting opportunities for broader interdisciplinary engagement. Overall, the study provides a comprehensive overview of the development and future trajectory of Green Supply Chain Marketing research and offers insights for scholars and practitioners seeking to align environmental responsibility with marketing and supply chain performance.